The judicial sector in Latin America and the Caribbean : elements of reform - Dakolias, Maria, 1965- (Washington, D.C. : World Bank, 1996)
"Professional analysis of essential elements of judicial reform, as provided in any country-specific review by the World Bank. As political and economic development continue, greater attention needs to be given to judicial reform. Basic elements of judicial reform include: guaranteeing judicial independence through changes in judicial budgeting, judicial appointment, and disciplinary systems; adopting procedural reforms; enhancing public access to justice; incorporating gender issues in the reform process; and redefining/expanding legal education and training"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references.
Keywords: Justice, Administration of -- Latin America; Law reform -- Latin America